Literacy, language and the Peter Blake Principle - Brown-Blake, Celia (International Journal of Speech, Language and the Law, 2004)
This paper examines the implications of the distinctions between speech|and writing for the operation of a particular legal device in the Jamaican common law known as the Peter Blake principle. The principle allows a cross-examiner to test the evidence and credibility of a witness by putting a document to a witness. The witness is required to look at it and thereafter the cross-examiner will ask him questions on the|document. Issues concerning the efficacy of the principle arise where a textual document is put to a witness who is unable to read and the document is read aloud to him/her. This paper explores the nature of the possible consequences that emanate from a written to oral text conversion and their ramifications for the operation of the Peter Blake principle when it is applied in the context of a non-literate witness. It does so with particular focus on police station diaries and indicates the danger of the likelihood of a compromise of the value of this critical legal device in situations where there is a mere reading aloud to a non-literate witness, without any further adjustment, of police station diary texts